Insitu Self-Assembly of Bacterial Cellulose on Banana Fibers Extracted from Peels. Issue 9 (1st September 2020) - Naeem, Muhammad Awais; Siddiqui, Qasim; Mushtaq, Muhammad; Farooq, Amjad; Pang, Zengyuan; Wei, Qufu
ABSTRACT: In this research work, in-situ self-assembly approach was used the first time, to cultivate bacterial cellulose on the surface of fibers, extracted from banana peels. The characterization was performed using SEM, FTIR, and single fiber tensile test in order to determine the surface morphology and mechanical properties of modified fibers. As-prepared hybrid fibers exhibited comparatively better mechanical properties, which can be attributed to the self-assembly of bacterial cellulose on banana fibers' surface. Overall, this research work suggests a novel route for fiber extraction from banana peels and to use them for the preparation of bio nano-composites with improved mechanical properties.